Pengaruh Bauran Pemasaran Dan Kualitas Pelayanan Jasa Pendidikan Terhadap Kepuasan Santri Pondok Pesantren Al-Mushlih Karawang - Jihan Nursuci; Arif Fadilla (Peneliti.net, 2022)
The purpose of this research is to know the relationship between Marketing Mix and service quality. This study aims to determine the effect of the marketing mix and service quality on the satisfaction of the students of the Al-Mushlih Islamic Boarding School, Karawang. The method used in this research is descriptive and verification with a quantitative approach. The sample used in this study was 120 samples with Accidental Sampling sampling technique. The data analysis technique used in this research is using path analysis techniques. The hypothesis testing used is partial and simultaneous hypothesis testing. The results of this study are that there is a relationship between the Education Services Marketing Mix (X1) and the Education Service Quality (X2) has a strong and unidirectional relationship because it has a positive and significant value of 0.763. There is a partial influence of the Education Services Marketing Mix on Consumer Satisfaction of 27.9%. The quality of education services partially on consumer satisfaction is 28.6%. The Marketing Mix of Educational Services and the Quality of Educational Services simultaneously have a positive and significant influence on Consumer Satisfaction. The influence of the marketing mix of educational services and the quality of educational services is 56.5%. This means that the marketing mix of educational services (X1) and the quality of educational services (X2) has a contribution to consumer satisfaction (Y) of 56.5% while the remaining 44.5% is the contribution of other variables (ε) which were not examined.